Nilai mencapai kehidupan sejahtera: pandangan Hamka - Abdul Rahman Abdul Aziz, (Universiti Kebangsaan Malaysia, 2009)
The focus of this article is on the thoughts of a prominent Indonesian Islamic scholar i.e. Hamka. He was a literary artist, da’ei, and leader of an Islamic movement. His influence persists throughout the Malay world, namely Malaysia, Singapore, Brunei and the Southern Thailand. Although he passed away 30 years ago, his thoughts still remained in the hearts and minds of Muslims in the Malay world. Hamka wrote extensively on philosophical issues, novels, and ethics of self-development related to the values of human happiness or human well-being. Thus the aim of this article is to discuss Hamka’s thoughts on the definitions and meanings of humanistic values portrayed in his writings. The discussion in this article is mainly focussing on two of Hamka’s writings i.e. Tasauf Moden (Modern Philosophy) and Tuan Direktur (Mr. Director)